2017
DOI: 10.1371/journal.pone.0186346
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the risk of gingival disease in patients with rheumatoid arthritis

Abstract: Gingival disase and rheumatoid arthritis (RA) are linked at both the epidemiologic and pathogenesis levels. In this study, we aimed to identify environmental factors associated with RA and gingival disease and to investigate factors that protect the gingival tissue in RA patients. This retrospective study analyzed 754 RA patients with gingival disease selected from the NHANES database who completed the mobile examination center interview/examination between 1999 and 2004. Data collected included demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Among the inflammatory diseases, periodontitis is one of the most common oral conditions with an inflammatory profile. 1,2 This disease is an inflammatory impairment that may mildly affect gingiva, resulting in bleeding, halitosis, and edema, or result in severe damage of dental supporting tissues, promoting damage of the gingiva, periodontal ligament, loss of attachment of alveolar bone and tooth loss. 3,4 The pathogenesis of periodontitis is a result of complex interactions between the periodontal pathogens and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Among the inflammatory diseases, periodontitis is one of the most common oral conditions with an inflammatory profile. 1,2 This disease is an inflammatory impairment that may mildly affect gingiva, resulting in bleeding, halitosis, and edema, or result in severe damage of dental supporting tissues, promoting damage of the gingiva, periodontal ligament, loss of attachment of alveolar bone and tooth loss. 3,4 The pathogenesis of periodontitis is a result of complex interactions between the periodontal pathogens and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Some single-center studies from China have reported the incidence of postoperative complications of CD to be 5.92-32.3%, among which the incidence of enterocutaneous stula accounted for 8.3-58.6% of the total complication rate. 4 Previous international studies have reported the incidence of postoperative complications of CD to be 5.0-40.9%, with the incidence of enterocutaneous stula accounting for 6.0-76.4% of the total complication rate. 5,6 Postoperative intestinal stula can cause changes such as abdominal infection, malnutrition, and multiorgan failure.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies showed an increased prevalence of RA in patients with PD [25,26]. Others demonstrated the presence of RF in the gingiva, saliva, and serum of patients having PD [27,28].…”
Section: Discussionmentioning
confidence: 99%